Pelatihan Bilal Khotbah Jum'at di Sukolilo Labang Bangkalan - M. Thohir; Shonhaji Shonhaji; Moh Sholeh (Institut Teknologi dan Bisnis Semarang, 2023)
Khotib and Bilal Training for Youth in Sukolilo Labang Village. The formulation of the problem raised in this community service activity relates to the function of the khutbah and Bilal which are very important in the da'wah of Muslims, so the sermon must be delivered in a language that is easily understood by the congregation (perhaps the local language), except for the pillars of the sermon. To find alternative solutions to the above, a khatib and bilal training was held for youth in Sukolilo Labang Village. The objectives of this PkM activity are: 1. To equip youth with knowledge about khatib and Bilal, 2. To equip youth as preachers in a better change, and 3. To increase knowledge and morals in society through Friday sermons that touch the hearts of the congregation 'Ah. The problem-solving framework designed in the PKM activities in the form of implementing these training activities is: 1. Explanation of the concept of khatib and Bilal, the philosophical basis of which is good, followed by exercises to find the root of the problem according to conditions, 2. Designing and implementing Khatib and Bilal Training accompanied by supervision and guidance of youth in designing sermon scripts, 3. Practicing Khatib and Bilal Activities, 4. Evaluation of training results. Based on interviews, questions and answers and direct observation during the activity, this community service activity yielded the following results: first, increased knowledge and understanding of youth about procedures as khatib and bilal, and second, increased youth skills regarding procedures as preachers and bilal so that it is possible can participate as khatib and bilal in Friday prayer activities, as well as Eid al-Fitr and Eid al-Adha prayers.